(untitled) (Research, Society and Development, 2021)
Stachys byzantina K. Koch, known in Brazil as “fish from the garden or pulmonary”, belongs to the Lamiaceae family, and is an unconventional food plant (Ufp). Reports show that this plant has different biological activities such as antioxidant, anti-inflammatory and microbiological inhibition. Due to its biological activities and the importance of rescuing species of Ufp, capable of presenting different applications, whether in natura, dehydrated form or through the extraction of volatile oils, which have great potential for use in industry. In this work, the drying kinetics and antimicrobial activity of essential oil and hydrolate, obtained by means of hydrodistillation and steam drag methods, were determined. For drying kinetics, the best fit mathematical model was the logarithmic one, with a coefficient of determination of 0.9995 and Chi-square 0.0007. Antimicrobial activity was performed by disk diffusion test against Bacillus cereus, Listeria monocytogenes, Staphylococcus aureus, Escherichia coli and Salmonella gallinarium bacteria. It was possible to observe antibacterial activity against L. monocytogenes for both the essential oil (0.9 cm halo) and the hydrolate (1.0 cm halo), both obtained by steam drag using dry leaves at a temperature of 80 °C . In the consulted literature, no reports were found on the antibacterial activity of the essential oil and/or hydrolate of this Ufp against L. monocytogenes bacteria. Thus, these results may guide future work with the application of this plant material as an antimicrobial compound, since L. monocytogenes is a pathogenic contaminant in production lines in food industries.